Transforming industrial R&D into an entrepreneurial organisation: implications of organisational design on enabling innovation. (2016) - Brook, Jacques W.
This study has sought to gain insight into the issue of transforming industrial R&D into an entrepreneurial organisation. It focused on how organisation innovation enables a successful transformation. First, our findings show that a strategy of industrial R&D to integrate intrapreneurship as part of its core capabilities led to an organisation wide innovation that required a transformational change. This strategic reorientation could not be executed through a regular reorganisation. Second, a transformation associated with organisation innovation appears to be successful. Innovating the structure, business processes, HR and rewards, consistently appears to be a determinant of success. This approach leads to a better adoption and diffusion of new practices across the organisation. For example, the implemented ambidextrous structure was supported by lateral processes, HR with an ambidextrous mind-set and a rewards system encouraging collaboration across the organisation. Third, the new operating model of industrial R&D reconciles intrapreneurship with science-based research.